Not too tough

Algebra Level 1

For any positive real number x find the value of

( x a x b ) a + b × ( x b x c ) b + c × ( x c x a ) c + a \left(\dfrac{x^a}{x^b}\right )^{a+b} \times\left(\dfrac{x^b}{x^c}\right )^{b+c} \times\left(\dfrac{x^c}{x^a}\right)^{c+a}


The answer is 1.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Curtis Clement
Jul 31, 2015

Using the properties of exponents the expression can be written as: ( x a b ) a + b × ( x b c ) b + c × ( x c a ) c + a \ ( x^{a-b} )^{a+b} \times\ ( x^{b-c} )^{b+c} \times\ ( x^{c-a} )^{c+a} = x a 2 b 2 . x b 2 c 2 . x c 2 a 2 \ = x^{a^2 -b^2} . x^{b^2 -c^2} . x^{c^2 -a^2} = x ( a 2 b 2 ) + ( b 2 c 2 ) + ( c 2 a 2 ) = x 0 = 1 ( x > 0 ) \ = x^ {(a^2 -b^2) + (b^2 -c^2) + (c^2 -a^2)} = x^0 = 1 \ (x > 0) Also, note that the exponent of x has to be zero for the expression to be a constant (as implied by the question). This can be proven with logs... x ϕ = C ϕ l o g ( x ) = l o g ( C ) \ x^{\phi} = C \implies\ \phi log (x) = log (C) Now log(x) varies as x varies, so we must have ϕ \phi = 0 for the LHS to be equal to a constant, given as log(C). x ϕ = x 0 = 1 \therefore\ x^{\phi} = x^0 = 1

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...